An Affirmation of Faith for the Mentally Retarded - Perske, Robert (Journal of religion, disability & health, 2003)
Because of the special needs of people with mental retardation, a statement of faith that emphasizes a loving God who accompanies us in our struggles is especially relevant. This statement declares that people with mental retardation are part of the community of faith, highlighting their efforts to give themselves in worship to God and service to others. Therefore, life in community with God and the people of faith is affirmed as good.